Documentary games: an investigation into the amalgamation of the filmic mode of 'documentary' and the gaming medium through the case studies on the film Bowling for Columbine (2002) and videogame, Super Columbine Massacre RPG (2005) - Harding, Kelly (My University, 2012)
4 Abstract This research report investigates the concept of documentary games, an amalgamation of ‘reality’ (documentary) and ‘escapism’ (gaming), and the way in which these games have evolved into a new, emerging and widely used of storytelling and art. A comparison will be made between two case studies from different mediums: a film, Bowling For Columbine and a videogame, Super Columbine Massacre RPG. By exploring the differences and similarities of these two mediums and how they are defined, I intend to demonstrate how gaming has progressed and merged with documentary (film) to create a new art form. The aim of the research report is to determine whether videogames can in fact be viewed and categorised as ‘documentary’ games by specifically analysing the documentative aspects of one videogame, Super Columbine Massacre RPG! created by documentary filmmaker, Daniel Ledonne.
M.A. University of the Witwatersrand, Faculty of Humanities, 2012